Implementation of the Principle of Caution by Land Deed Officials in Making Deeds to Prevent Land Disputes in North Sulawesi Province - Bin Syeban, Salim Filza Taufiq; Purnawan, Amin (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract.The purpose of this study is to determine and analyze the application of the principle of caution of Land Deed Officials in making deeds to prevent land disputes and to determine and analyze the responsibility of Land Deed Officials who do not apply the principle of caution in making deeds. The method used by the researcher is empirical juridical with an empirical approach. The specifications of this study are descriptive analytical. The types of data used are primary data sourced from field studies and secondary data sourced from materials obtained from literature studies. Based on the results of the study that: 1) Land Deed Officials in North Sulawesi apply the principle of caution in making deeds to prevent land disputes as mandated by Government Regulation Number 37 of 1998 as amended by Government Regulation Number 24 of 2016 concerning Land Deed Officials and its implementing regulations. Among the implementation of the principle of caution carried out by PPAT are: first, reading and explaining the contents of the deed to the parties, second, not making a deed for himself and his family, third, carrying out the obligation to check the conformity/validity of the certificate and other records at the Land Office and fourth, rejecting the making of a deed that is not based on formal data. 2) The responsibility of the Land Deed Making Officer who does not implement the principle of caution in making a deed is ethical/moral responsibility and legal responsibility. Legal responsibility is divided into civil responsibility, criminal responsibility and administrative responsibility.Keywords: Land Deed Makers; Legal Accountability; Principle of Prudence; Officials.